2022
DOI: 10.1111/iej.13714
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of complete and partial pulpotomy in mature permanent teeth with symptomatic irreversible pulpitis: A randomized clinical trial

Abstract: Aim The study aimed to compare the outcome of complete pulpotomy (CP) and partial pulpotomy (PP) techniques when utilised for the management of mature permanent teeth with carious pulpal exposure and symptomatic irreversible pulpitis (SIP). Methodology The study protocol was registered with ClinicalTrials.gov (NCT04397315). One hundred and six permanent mandibular molars with carious pulpal exposure and clinical diagnosis of SIP with periapical index ≤2, from patients aged between 18 and 40 years were randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 25 publications
(59 reference statements)
1
45
6
1
Order By: Relevance
“…In our study, those patients who intraoperatively showed signs indicative of necrosis (partial/total necrosis and absence of bleeding) and cases in which bleeding could not be stopped (within 10 min) were excluded from the study altogether to ensure appropriate case selection for VPT. The use of the results of Ramani et al (2022) or Cushley et al (2019) would have influenced the sample size calculation; however, at the time of planning, Elmsmari et al (2019) was the most appropriate study to use for sample size calculation being a systematic review with meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, those patients who intraoperatively showed signs indicative of necrosis (partial/total necrosis and absence of bleeding) and cases in which bleeding could not be stopped (within 10 min) were excluded from the study altogether to ensure appropriate case selection for VPT. The use of the results of Ramani et al (2022) or Cushley et al (2019) would have influenced the sample size calculation; however, at the time of planning, Elmsmari et al (2019) was the most appropriate study to use for sample size calculation being a systematic review with meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of histological and clinical evidence suggests that the cariously exposed pulp even if associated with signs and symptoms indicative of irreversible pulpitis may not actually be beyond conservative treatment (Ramani et al, 2022; Ricucci et al, 2014). In response to the invasion of bacteria and release of their by‐products, the pulp has been shown to react in a graded manner that progresses gradually in an apical direction (Heyeraas & Berggreen, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, more scholars began to study related content [76,77]. For teeth with deep caries exposed pulp rather than irreversible pulpitis, partial pulpotomy is effective [38], while for teeth with irreversible pulpitis, total pulpotomy has a higher success rate [59,[78][79][80]. In 2021, a review analyzed the treatment results of total pulpotomy and partial pulpotomy in recent years.…”
Section: Pulpotomy Of Mature Permanentmentioning
confidence: 99%
“…The pulpotomy group had considerably reduced analgesic consumption, showing that the short-term goal of pain management was better attained with pulpotomy. This might be because pulpotomy ensures better clearance of infected and inflamed pulp, resulting in a faster recovery from pain 18 . In order to standardize the data and link analgesic usage to postoperative discomfort or pain change, just one type of painkiller was administered.…”
Section: Discussionmentioning
confidence: 99%